4D mixed chaotic system and its application to RGB image encryption using substitution-diffusion. (September 2021) - ul Haq, Tanveer; Shah, Tariq
Abstract: Low order chaotic maps has many distinct physiognomies, such as strong sensitiveness to initial conditions, parameters, better unpredictability, distinct random like complex temporal behavior and so on. This results the demand of new generators for chaotic systems with complicated dynamics but simple designs. In this work, a 4D mixed chaotic map with hyper-chaotic properties and high randomness behavior has been constructed by using the 1D Sine map and the 2D Thinker bell map. Furthermore, by using the proposed chaotic system and symmetric group S 8  permutation, a novel image encryption scheme is introduced to explore the applications of the proposed chaotic system. The action of symmetric group S 8 increases the key size by a factor of (8!) 65536 for an image of size 256  ×  256 which results a strong encryption structure to resists the well-known attacks. Simulation results on different images and extensive security analysis demonstrate that the proposed approach has adequate properties in image encryption.